Evaluating China's Water Security for Food Production: The Role of Rainfall and Irrigation. Issue 20 (21st October 2019) - Zhu, Wenbin; Jia, Shaofeng; Devineni, Naresh; Lv, Aifeng; Lall, Upmanu
Abstract: China's water stress and its pressure on food security is a widely recognized crisis. A framework is proposed and applied at the provincial level to evaluate China's water security for food production. It is based on a water stress index that accounts for the deficit between water supply and aggregate demand of 23 major field crops over the study period (1961–2015). The water demand is estimated based on method recommended by the Food and Agriculture Organization of the United Nations. The water supply is composed of rainfall and irrigation. Consequently, the water security of both rainfed and irrigated agriculture is evaluated in our research, and the respective contribution of rainfall and irrigation is distinguished. Suggestions regarding adjustment in irrigation investment and planting area are proposed for practical application. The framework also holds great potential to investigate the impact of climate change and the virtual water flow of crops. Plain Language Summary: With 7% of the world's arable land and 6% of its water resources, China has to feed 20% of the world's population. Consequently, China's water stress and its pressure on food security is a widely recognized crisis. A framework is proposed in our research to evaluate China's water security for food production. It is mainly designed to answer the following three questions critical to China's food security but have not been systematically addressed in the literature. How much water is required under China's current agriculture planting structure? What is the respective role of rainfall and irrigation in meeting this requirement? What is the status of water security for China's rainfed and irrigated agriculture? The above three questions are answered based on a water stress index that accounts for the deficit between water supply and aggregate demand of 23 major field crops over the study period (1961–2015). We have also proposed suggestions regarding water security for food production from the framework. For future use, our proposed framework lays the groundwork to investigate the virtual water flow of crops. Climate change signals can also be incorporated into this framework to inform climate‐driven water risk for agriculture. Key Points: A new framework is proposed to evaluate water security for food production Respective contribution of rainfall and irrigation to water security is distinguished Spatial patterns of China's water security for food production are investigated